Penguatan Pengetahuan Masyarakat dan Literasi Keuangan Mengenai Konsep Perbankan Syariah dalam Memenangkan Persaingan Bisnis - Agung Asdi Pratama; Pristiyono Pristiyono; Meisa Fitri Nasution (Ekonomis: Journal of Economics and Business, 2023)
The level of competition in the Sharia banking business nationally is increasingly very competitive, thus providing challenges and threats to other financial institutions, especially conventional banking. Islamic banking measures the extent to which Sharia-based financial literacy is in winning business competition in Labuhanbatu Regency. The intended population is all Rantauprapat Bank Syariah Indonesia (BSI) customers. Determination of the writer's sample using the slovin formula in order to obtain a sample of 100 people. The variables examined in this study are public knowledge, Sharia-based financial literacy, the concept of Islamic banking, competitive advantage. Data collection technique through google form with purposive sampling technique. Data analysis uses the SmartPLS 4.0 application approach to solve the problems tested. Based on the research results in a description of the reasons customers use to choose Islamic banking because the product information varies. From testing the hypothesis, it shows that public knowledge and financial literacy are key to the concept of Islamic banking, then public knowledge and financial literacy are the keys to winning business competition in Labuhanbatu Regency. From the research results calculated using outer loading on each variable declared valid because it is greater than the value of 0.5. And has an R-square value of Islamic banking concept of 0.357 or 35.7% and an R-square value of business competition of 0.765 or 76.5%.